Confrontation between Saudi Arabia and Iran in Persian Gulf in the Late 20th - early 21st Centuries - V. A. Kuzmin; N. V. Sokolov (Научный диалог, 2017)
The article is devoted to the problem of the struggle for leadership in the Persian Gulf region in the late 20th - early 21st centuries. The article covers developments in the region, starting with the victory of the Islamic revolution in Iran in 1979. The main attention is paid to the international implications of the Iranian revolution, years of the Iran-Iraq war, the invasion of Kuwait by Iraq, international forces operations against these aggressive actions by Iraq. The question is that after the victory of the Islamic revolution, Iran emerged on the regional stage as a clear contender for the role of a new leader. It is shown that the main enemy of Iran is the Kingdom of Saudi Arabia. Special attention is paid to identifying the various forms and methods through which Iran and Saudi Arabia are fighting for leadership in the Persian Gulf. Novelty of research consists in that it is carried out on the basis of the analysis of a very wide range of sources and literature in the Arabic language, loosely used in the works of other scientists. The research urgency is caused by the fact that the study of the above historical events allows a better understanding of some contemporary phenomena and processes occurring in the middle East.